Cholangiographic Study of the Location of Papilla of Vater - Beguiristain, Alberto; Pignata, Daniel; Pomi, Jorge; Estefan, Alberto (Cirugía del Uruguay, 1979)
An analysis of 186 cholangiographies sho'wed 12 cases of vertical common bile ducts; 9 of these ended in the inferior duodenal genu and 3 in the third duodenal portian.